TRADE AND NUTRITION: POLICY COHERENCE FOR HEALTHY DIETS - Dongyu, Qu (The State of Agricultural Commodity Markets, 2024)
Trade is integral to our agrifood systems as it fulfils the fundamental function of moving food from surplus to deficit regions, thus contributing to food security globally. Global food markets connect people and countries across the globe, contribute to efficient natural resources use worldwide, facilitate the supply of sufficient, safe and diverse food and generate income for farmers and those employed in the food and agricultural sectors. Trade is inherent to the economic, social and environmental dimensions of sustainable development. It is closely related to economic growth, it interacts with people and links with the environment. The rapid globalization of food markets has raised concerns about the potential impacts of progressively increasing food trade on societies. The 2024 edition of The State of Agricultural Commodity Markets (SOCO 2024) explores the complex linkages between food trade and nutrition and generates evidence to identify how trade affects dietary patterns and nutritional outcomes. The report examines the intersection of trade policies and nutrition measures and provides policymakers with an understanding of how to address nutrition objectives in the changing landscape of global agrifood systems.